Implementasi Sistem Monitoring Server Berbasis Linux pada ICT Politeknik Negeri Tanah Laut - Baitul Izza, Khomsah Wiyana; Eka Sholeha, Wahyu (Journal Information Technology Trends (JITRENDS), 2025)
This study aims to design and implement a Linux-based server monitoring system at the ICT State Polytechnic of Tanah Laut. The background of this research is driven by the current lack of an integrated monitoring system, which can lead to downtime and service disruptions. The proposed system monitors key parameters such as CPU utilization, memory, storage, and network in real-time, utilizing tools like Prometheus and Grafana. The research methodology includes literature review, needs analysis, system design, implementation, and evaluation of system effectiveness. The expected outcomes are increased reliability and availability of server services, as well as a reduction in the manual workload of the ICT team. With this monitoring system, campus operations are expected to run more efficiently and support the achievement of academic and administrative goals of the Tanah Laut State Polytechnic.